2016
DOI: 10.1021/acs.langmuir.6b00245
|View full text |Cite
|
Sign up to set email alerts
|

Using ApoE Nanolipoprotein Particles To Analyze SNARE-Induced Fusion Pores

Abstract: Here we introduce ApoE-based Nanolipoprotein particles (NLP) – soluble, discoidal bilayer mimetic of ~23 nm in diameter, as fusion partners to study the dynamics of fusion pores induced by SNARE proteins. Using in vitro lipid mixing and content release assays, we report that NLPs reconstituted with synaptic v-SNARE VAMP2 (vNLP) fuse with liposomes containing the cognate t-SNARE (Syntaxin1/SNAP25) partner, with the resulting fusion pore opening directly to the external buffer. Efflux of encapsulated fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 41 publications
4
41
0
Order By: Relevance
“…Conductance was low when ~15 nm MSP nanodiscs with eight copies of v-SNAREs (vMSP8) were used (Wu et al, 2016), but not affected when ~23 nm NLPs bearing 30 v-SNAREs were employed (vNLP30). These results are consistent with those of Bello et al (2016), who showed that progressively larger cargo could be released from t-SNARE liposomes during fusion with vNLPs as the v-SNARE copies per NLP was increased. Second, conductance of n small pores in a single NLP would be additive, giving total conductance equal to Gpo=n × gpo, where gpo is the mean open-pore conductance of a small pore.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Conductance was low when ~15 nm MSP nanodiscs with eight copies of v-SNAREs (vMSP8) were used (Wu et al, 2016), but not affected when ~23 nm NLPs bearing 30 v-SNAREs were employed (vNLP30). These results are consistent with those of Bello et al (2016), who showed that progressively larger cargo could be released from t-SNARE liposomes during fusion with vNLPs as the v-SNARE copies per NLP was increased. Second, conductance of n small pores in a single NLP would be additive, giving total conductance equal to Gpo=n × gpo, where gpo is the mean open-pore conductance of a small pore.…”
Section: Resultssupporting
confidence: 92%
“…We estimate that 4–5% of the docked vNLPs undergo fusion with the flipped t-SNARE cells over the course of ~20 min (Figure 2—figure supplement 1). In comparison, fusion between v-SNARE NLPs and t-SNARE liposomes yields a similar extent of lipid mixing over the same period (Bello et al, 2016).
10.7554/eLife.22964.004Figure 2.vNLPs induce lipid mixing when incubated with flipped t-SNARE cells (tCells).( a ) Schematic of the assay.
…”
Section: Resultsmentioning
confidence: 99%
“…ApoE‐based scaffolds afford ~ 25 nm discs that can accommodate ~ 15 v‐ SNARE s per face . With these discs, the fusion pore can expand to ≳ 10 nm diameter with little obstruction from the scaffold ring . (B) NDs reconstituted with neuronal v‐ SNARE s are mixed with small liposomes reconstituted with complementary neuronal t‐ SNARE s. Bulk cargo release is monitored by an increase in the fluorescence of a cargo‐sensitive dye present in the bath.…”
Section: Nanodisc‐based Fusion Assays: a New Look At Fusion Poresmentioning
confidence: 99%
“…This suggested a very small and/or transient pore could be induced by a single SNARE complex (which is sufficient to maintain two bilayers in close proximity [54]), but a larger/ longer-lived pore that allowed detectable calcium release required three or more complexes [36]. Bello et al [35] extended these studies by systematically varying both the size of cargo encapsulated into t-SNARE liposomes and v-SNARE copy numbers in larger,~23 nm NLPs. There was a positive correlation between v-SNARE copies per disc and the size of cargo that could be released efficiently [35].…”
Section: Nanodisc-liposome Fusionmentioning
confidence: 99%
“…We follow a protocol developed in the Rothman lab for making these discs, described in ref. 31 , and Stroeva and Krishnakumar [32]. …”
Section: Methodsmentioning
confidence: 99%